Comparing equestrian helmets with and without rotational technology using an equestrian concussive-specific helmet test protocol - Murphy, A.; Post, A.; Gilchrist, M. D.; Hoshizaki, B. (Sports Engineering, 2024)
Equestrian sports are popular around the world; however, sustaining injuries can occur, with the most common catastrophic injury events involving the head. Helmets are used to help reduce the risk of head and brain injury; however, the rates of concussion remain unaffected. Recently, technology designed to reduce the rotational accelerations associated with concussion have been incorporated into equestrian helmets, but it is unknown the efficacy of these technologies under the impact conditions within this sporting environment. The purpose of this research was to investigate the efficacy of rotational technology in managing linear and rotational acceleration, rotational velocity, and predicted maximum principal strain of the brain using a test protocol representative of equestrian fall events. Helmets with and without rotational technology were fitted to a Hybrid III headform and impacted under conditions that simulated the helmet loading characteristics of falling in equestrian sports. The resulting linear and rotational acceleration time histories from the headform was then used for finite element modeling to predict the strain to the brain tissues. The helmets that included rotational technology did lead to a significant reduction in the peak resultant rotational accelerations and rotational velocity at the rear boss location, and a reduction in strain for the side location under the high-compliance condition. The results from the present study show that the helmet with rotational technology worked under certain impact conditions; however, it is not a universal improvement.